ASSESSMENT OF OUTCOME OF THE REPAIR OF VESICO VAGINAL FISTULA - HASSAN , S; AKHTAR , M; AFZAL , U (Biological and Clinical Sciences Research Journal, 2023)
The retrospective study was conducted in the Urology & Gynecology Department from January 2022 to January 2023 to ascertain the outcomes of VVF repair in the local population. The study was conducted on a total of 20 patients. Reno ureteric configuration in all patients was documented using intravenous urogram (IUV) renal ultrasonography. A cystogram with lateral and anteroposterior views was taken. Perioperative details were recorded, including approach (vaginal or abdominal) and interposition flap (martius flap /omentum/ local peritoneum). The procedure was successful if the patient reported continence. 6 (30%) patients had complex fistulas, and 14 (70%) had simple fistulas. In the Open technique, 13/16 (81.25%) patients had successful VVF repair, while in the laparoscopic group, 4/4 (100%) had the successful group. The average blood loss during the laparoscopic technique was 100 ml, and for open repair, 600 ml. The operative time for the laparoscopic technique was 205 minutes, and for the open technique, it was 150 minutes. The follow-up period ranged from 2 to 25 months. 3 of the 16 patients undergoing open repair had fistula recurrence; the laparoscopic group did not report any recurrence. The mean duration of hospital stay for open and laparoscopic techniques was 24 days and 10 days, respectively. Surgical VVF repair provides a definitive cure. Complex fistulas are at an increased risk of failed repair. Primary repair has the highest success rate. The outcome depends upon case selection and principles of repair.